2012
DOI: 10.1039/c1ja10235d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the hydrogen contained in amorphous silicon thin films on a pulsed radiofrequency argon glow discharge coupled to time of flight mass spectrometry. Comparison with the addition of hydrogen as discharge gas

Abstract: Thin film solar cells technology based on hydrogenated amorphous silicon (a-Si:H) has undergone a great expansion during recent years. Pulsed radiofrequency glow discharge time-of-flight mass spectrometry (rf-PGD-ToFMS) is able to perform depth profiling analysis of coated materials, providing an excellent tool for rapid and high sensitive chemical characterisation of photovoltaic devices. The hydrogen concentration on a-Si:H thin films is around 10%, which represents a challenge for quantitative depth profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 24 publications
(27 reference statements)
2
16
0
Order By: Relevance
“…The optimum conditions were 600 Pa and 90 W, similar to previous experiments [21]. As expected [7,22], higher analytical signals were obtained in the afterpeak region of the pulse profile, and so the afterpeak will be the only temporal region in the GD pulses shown throughout this Results and Discussion section.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…The optimum conditions were 600 Pa and 90 W, similar to previous experiments [21]. As expected [7,22], higher analytical signals were obtained in the afterpeak region of the pulse profile, and so the afterpeak will be the only temporal region in the GD pulses shown throughout this Results and Discussion section.…”
Section: Resultssupporting
confidence: 63%
“…On the other hand, although polyatomics attributable to recombination processes in the GD dynamic plasma are typically produced at the end of the afterglow region, the exact shape depends on the particular polyatomic. Finally, for silicon measurement similar results to those previously reported in experimental works carried out in our group were found [7,21]. Although several polyatomic interferences can occur for the three Si isotopes (e.g., Si + was 18.1, which corresponds to an 8% deviation from the natural isotope abundance ratios.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…However, to know the layer thickness and composition as well as possible concentration gradients, further investigations to develop proper quantification methods are needed. In this vein, it should be stated that the presence of hydrogen on a-Si:H thin films represents a challenge for quantitative analysis because of the so-called hydrogen effect [19], and possible hydrogen sources have been evaluated in our previous works by rf-PGD-OES and rf-PGD-MS in a-Si:H thin films [20,21]. By both analytical methods, we observed that molecular hydrogen added to the discharge gas plays a more critical role than the endogenous hydrogen present in the sample itself (samples with hydrogen content below 10% atomic).…”
Section: Introductionmentioning
confidence: 99%